2014
DOI: 10.1111/vde.12114
|View full text |Cite|
|
Sign up to set email alerts
|

On the role of survivin as a stem cell biomarker of canine hair follicle and related tumours

Abstract: These findings suggest that survivin could play an important role in the maintenance of the hair follicle cycle as well as in tumour initiation and maintenance of cancer stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, survivin, a member of the inhibitor of apoptosis proteins associated with tumor initiation and progression and maintenance of stem cells, 41 showed partial co-localization with CK15 in trichoepitheliomas and trichoblastomas, suggesting a role for survivin in the maintenance of cancer stem cells in these HF tumors. 5…”
Section: Hair Follicle Neoplasms and Stem Cellsmentioning
confidence: 99%
“…Interestingly, survivin, a member of the inhibitor of apoptosis proteins associated with tumor initiation and progression and maintenance of stem cells, 41 showed partial co-localization with CK15 in trichoepitheliomas and trichoblastomas, suggesting a role for survivin in the maintenance of cancer stem cells in these HF tumors. 5…”
Section: Hair Follicle Neoplasms and Stem Cellsmentioning
confidence: 99%
“…At present, Survivin has gained marked interest in the field of tumor research. The protein is tumor specific, which means that it is only expressed in tumor and embryonic tissues, and is closely associated with tumor differentiation, proliferation, invasion and metastasis (20,21). The expression of the Survivin gene has been identified to be upregulated in nasal type natural killer (NK)/T cell lymphoma cells and has been found to be significantly correlated with the expression of p53 and B cell lymphoma 2 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that survivin expression was downregulated by CUR and CUR + BUS (Figures 5(a) and 5(b) ; Table 1 ). Survivin is an important IAP that tends to be overexpressed in cancer cells [ 51 ], including cancer stem cells [ 52 , 53 ], which exerts antiapoptotic effects via various mechanisms. For example, survivin inhibits caspase-dependent apoptosis through cooperation with XIAP, inhibits the SMAC-XIAP complex, and interferes with caspase-3/caspase-9 [ 51 ] ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…CUR alone and especially CUR + BUS decreased survivin expression in KG1a cells (consistent with the results of apoptosis showed in Figures 3(a) and 3(b) ). Growing evidence has demonstrated that downregulating or inhibiting survivin could induce apoptosis and eradicate cancer stem cells or LSCs [ 52 , 54 – 56 ]. This suggests that CUR may induce apoptosis and enhance BUS-induced apoptosis by downregulating the expression of survivin in KG1a cells.…”
Section: Discussionmentioning
confidence: 99%